Skipping breakfast leads to weight loss but also elevated cholesterol compared with consuming daily breakfasts of oat porridge or frosted cornflakes in overweight individuals: a randomised controlled trial. (13th November 2014) - Geliebter, Allan; Astbury, Nerys M.; Aviram-Friedman, Roni; Yahav, Eric; Hashim, Sami
Abstract: Eating breakfast may reduce appetite, body weight and CVD risk factors, but the breakfast type that produces the greatest health benefits remains unclear. We compared the effects of consuming a high-fibre breakfast, a non-fibre breakfast, or no-breakfast control on body weight, CVD risk factors and appetite. A total of thirty-six overweight participants (eighteen men and eighteen women) (mean age 33·9 (sd 7·5) years, mean BMI 32·8 (sd 4·7) kg/m 2 ) were randomly assigned to consume oat porridge ( n  = 12), frosted cornflakes ( n  = 12) or a water control ( n  = 12) breakfast daily for 4 weeks. Appetite ratings were collected on the first day and weekly thereafter. Before and after the intervention, body weight, composition, blood pressure and resting energy expenditure (REE) were measured and a fasting blood sample was collected. Across the 4 weeks, fullness was higher and hunger was lower in the oat porridge group compared with the control group ( P  < 0·05). Mean weight change over the intervention was significantly different in the control group (−1·18 (sd 1·16) kg) compared with both the cornflakes (−0·12 (sd 1·34) kg) and oat porridge (+0·26 (sd 0·91) kg) groups ( P  < 0·05). However, the control group also showed elevated total cholesterol concentrations relative to the cornflakes and oat porridge groups ( P  < 0·05). There were no differences between groups in changes in body composition, blood pressure, REE or other CVD risk factors. In conclusion, although skipping breakfast led to weight loss, it also resulted in increased total cholesterol concentrations compared with eating either oat porridge or frosted cornflakes for breakfast.